Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X Materi Litosfer Di Sma Swasta Maharani Tahun Ajaran 2022/2023 - Asensiana Sanoin; Wolfgang Asindo Seran; Stefania Sonia Manek; Ivony Sarlin Asa (Journal Innovation In Education, 2023)
The problem at Maharani Private High School is that teachers or educators still use conventional methods so that students become passive in class and students' low understanding of the subject of geography, lithosphere material, which still contains many concepts, makes students feel bored, lazy, and this affects the results. learning and obtained by students whose grades do not meet the standard criteria for maximum completeness. The minimum standard for completion criteria (KKM) in geography subjects at Maharani Private High School is 75. This classroom action research aims to 1) find out the application of the jigsaw type cooperative learning model, 2) to find out the development of class X students' learning outcomes regarding lithosphere materials and types of rocks after using a jigsaw type learning model. The method used in this research is classroom action research or PTK using a jigsaw type cooperative learning model for class X students with research subjects of 20 students. The location of this research is Maharani Private High School for the 2022/2023 academic year, Weliman District, Malaka Regency, East Nusa Tenggara Province. This classroom action research was carried out in two cycles consisting of four stages including planning, observation, implementation and reflection. This research data was analyzed qualitatively descriptively. The results of this research show that using the jigsaw type cooperative learning model can improve the learning outcomes of class X SMA students on lithosphere material. The research results obtained for the first cycle of student learning outcomes were 6 students who completed with a percentage of 30% and as many as 14 students who did not complete or 70% of the 20 students, meanwhile, in cycle II the students who completed experienced an increase, namely 19 students. or as many as 95% and 1 student who did not complete or only 5% in cycle II. It can be concluded that using the jigsaw type learning model can significantly improve student learning outcomes in geography subjects on lithosphere material at Maharani Private High School for the 2022/2023 academic year.